A survey identifying leadership and research activities among Nurse Practitioners. Issue 5 (1st November 2020) - Ryder, Mary; Jacob, Elisabeth; Hendricks, Joyce
Abstract : Background: Nurse Practitioners are identified as the ideal conduit to transform healthcare delivery internationally. Healthcare transformation requires the application of leadership and research skills. Current literature has limited information on NPs as leaders or researchers in the nursing profession. Objectives: Determine if Nurse Practitioners identify themselves as leaders in nursing. Identify the leadership and research activities and influencing characteristics of Nurse Practitioners in Ireland and Australia. Establish similarities in leadership and research activities between Nurse Practitioners in Ireland and Australia. To identify if there is a relationship between leadership and research activities. Design: A quantitative electronic survey. Methods : A survey instrument was developed by combining two previously validated instruments. Nurse Practitioners in Ireland or Australia that had practiced within the last five years, and members of the respective professional association were included. Descriptive statistics were used to describe the findings and explore relationships in the data. Results : 14% ( n = 96) of Nurse Practitioners responded to the survey. Nurse Practitioners in Ireland and Australia identified themselves as leaders of the nursing profession. Nurse Practitioners work practices, leadership and research activities are similar in Ireland and Australia. The majority ( n = 55, 57%), of participants reported being research active. There was an association between perceived leadership and research activities among participants. Conclusion : Nurse Practitioners in both Ireland and Australia identify themselves as leaders of the nursing profession. There is no difference in reported work practices, leadership or research activities of Nurse Practitioners in both Ireland and Australia. There is an association between perceived leadership and research activity. Impact Statement: Nurse Practitioners in Ireland and Australia percieved themselves as leaders in nursing and this perception increases with research activity.